DINAMIKA KEBIJAKAN PERTAMBANGAN DI PROVINSI NTB DALAM PERSPEKTIF RPJMD DAN RTRW: KONFLIK AGRARIA, POLITIK RUANG, DAN IMPLIKASI LINGKUNGAN (STUDI KASUS PERTAMBANGAN RAKYAT SEKOTONG, LOMBOK BARAT) - Aryani, Dian; Ahmad Fathoni (Nusantara Hasana Journal, 2026)
West Nusa Tenggara Province is a region with an economic structure influenced by the extractive sector, including mining. On the one hand, the 2025–2029 NTB Regional Medium-Term Development Plan (RPJMD) emphasizes economic transformation and investment; on the other hand, the Spatial Planning (RTRW) serves as an instrument for spatial control and environmental protection. This study analyzes the dynamics of mining policies in both documents and their implications for artisanal mining in Sekotong, West Lombok Regency. A qualitative approach was used, using document analysis and a political ecology-based case study. The results indicate a structural tension between the orientation of extraction-based economic growth and commitment to environmental sustainability. The RTRW has not effectively integrated artisanal mining into the formal spatial planning framework, triggering agrarian conflict, land degradation, and health risks from mercury use. This article argues that reform of artisanal mining governance based on environmental carrying capacity and spatial equity is a prerequisite for the transition to a green economy in NTB.